STUDI HUKUM ISLAM TENTANG PENGANGKATAN ANAK (ADOPSI) DI UNIT PELAKSANA TEKNIS PERLINDUNGAN DAN PELAYANAN SOSIAL ASUHAN BALITA KOTA SIDOARJO - Mas’udah, Laily (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2020)
Implementation of Adoption in the Technical Implementation Unit for the Protection and Social Services of Sidoarjo City Toddler Child Care goes through 9 stages: prospective adoptive parents make an application letter for adoption of a child and written who the prospective adopted child is, filing the adoption administration filing stage, the adoption eligibility test stage with the holding of home visit I, submission of prospective adopted children to Prospective Adoptive Parents, the second step of the feasibility test of adoptive parents, the Recommendation Phase of the Social Service, the consideration phase by KEMENSOS in the PIPA Team session, certificate of granting permission for adoption of the child, finally the court's decision to determine the Court. The rights of children in the Technical Implementation Unit for the Protection and Social Services of Sidoarjo City Toddler Child Care have fulfilled the provisions contained in articles 4 through article 18 of Law Number 23 Year 2002 concerning Child Protection. In Islamic law, adoption of a child may not break the text between the child and his biological parents because it will have legal consequences for the child in terms of inheritance and marriage. In inheritance, adopted children are not included in the category of factors that cause someone to inherit each other, so that the adopted child has no right to inherit from his adopted father. If the adoptive parent wishes to give property to the adopted child it can be distributed by means of a grant while he is still alive or by will.